ADCP instrument status from ROV survey PS122/2_21-36 on 2020-01-21, survey 1 - Anhaus, Philipp; Katlein, Christian; Matero, Ilkka; Nicolaus, Marcel; Arndt, Stefanie; Krampe, Daniela; Lange, Benjamin Allen; Regnery, Julia; Rohde, Jan; Schiller, Martin (In: Anhaus, P et al. (2023): Water/ice velocity from remotely operated vehicle (ROV) surveys during the MOSAiC expedition 2019/20 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.953510, 2023)
Instrument status from the Nortek Aquadopp Profiler 2MHz acoustic doppler current profiler (ADCP) attached to the remotely operated vehicle (ROV) during the MOSAiC expedition 2019/20.
Keywords: ADCP; BEAST; MOSAiC expedition; Remotely operated vehicle (ROV); Sea ice